Online scheduling and pricing for electric vehicle charging. (1st February 2017) - Nejad, Mark M.; Mashayekhy, Lena; Chinnam, Ratna Babu; Grosu, Daniel
ABSTRACT: We design strategy-proof online scheduling and pricing mechanisms for Electric Vehicle (EV) charging in a competitive environment. EV drivers submit their requests for charging services dynamically over time, and they can name their own price on the charging services. The mechanisms schedule EV charging and determine charging prices considering the incentives of both EV drivers and power providers. In addition, our proposed online mechanisms do not assume availability of information about future demand. Our charging mechanisms are preemption aware, allowing flexibility on when charging takes place. This is in alignment with power providers' load-balancing goals. We perform extensive experiments to investigate the performance of our proposed mechanisms compared to that of the optimal offline mechanism. We analyze the various properties of our proposed mechanisms, in particular, we prove that they are strategy proof; that is, truthful reporting of price and amount of charging is a dominant strategy for self-interested EV drivers.